ANGKA KEBUNTINGAN SAPI LOKAL SETELAH DIINDUKSI DENGAN PROTOKOL OVSYNCH (Conception Rates of Local Cows after Induction with Ovsynch Protocols) - Mefrianti Efendi; Tongku Nizwan Siregar; Hamdan Hamdan; Dasrul Dasrul; Cut Nila Thasmi; Razali Razali; Arman Sayuti; Budianto Panjaitan (Jurnal Medika Veterinaria, 2015)
This study aims to know the effect of estrus synchronization using ovsynch method on local cow pregnancy rate. This study used 10 local cows without pregnant status and clinically healthy. All cows were divided into 2 treatment groups. Cows in group I (K1) were synchronized estrus using 5 mg/ml PgF2α intramuscularly with multiple injection patterns with intervals of 10 days. Group II (KII) was synchronized by ovsynch protocol, initiated with injection of 1ml GnRH on day-0. On the 7th day, the whole cows in K II were injected with 2 ml PgF2α then followed by re-injected with 1 ml of GnRH on the 9th day. Artificial insemination was performed 24 hours after GnRH last injection. The data were analyzed descriptively. The results showed that 3 cows in group I were diagnosed pregnant (60%), whereas in group II, 4 cows werediagnosed pregnant (80%). In conclusion, the estrus synchronization with ovsynch protocols provide a higher pregnancy rate than the conventional estrus synchronization.Key words: synchronization, ovsynch, GnRH, PgF2α